Pemberian Pupuk Kandang Ayam dan Pupuk Organik Cair (POC) Kulit Bawang Merah pada Tanaman Pakcoy (Brassica rapa. L) - Ferdi Yaldi; Dermawan Hutagaol; Efi Said Ali (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Al Azhar Medan, 2023)
Pakcoy (Brassica rapa L.) is a vegetable plant belonging to the Brassicaceae family. This study aims to determine the application and interaction of liquid organic fertilizer (poc) onion skin on Pakcoy (Brassica rapa L.) plants. This investigation was conducted between February and April of 2022 at Jl. Eka Suka Gg. Eka Suka XI Gedung Johor Kecamatan Medan Johor Provinsia Sumatera Utara. This investigation utilized a Factorial Group Randomized Design with 2 studied factors and 3 replicates, where the first factor was Hen house (A) with 3 levels and the second factor was replicate A0 = no treatment (control), A1=1.5 kg plot-1, A2 = 3 kg plot-1. The second factor is the concentration of Liquid Organic Onion Skin fertilizer (B) consisting of 4 levels, namely B0 = without treatment (control), B1 = 50 ml L-1 water, B2 = 100 ml L-1 water, B3 = 150 ml L-1 water. As parameters, plant height (cm), number of leaves (strands), leaf length (cm), leaf breadth (cm), and fresh weight of plants per sample (g) and per plot (g) were measured. The results revealed that the use of poultry house had a significant effect on plant height, leaf number, leaf length, leaf width, the fresh weight of plants per sample, and the fresh weight of plants per plot. Shallot peel liquid organic fertilizer has a very real effect on leaf length and fresh weight of plants per sample, a real effect on plant height and leaf width, but no real effect on leaf number and fresh weight of plants per plot. The interaction of hen house and onion peel liquid organic fertilizer has a significant impact on leaf length, leaf width, and fresh weight per plot, but no effect on plant height, number of leaves, and fresh weight per sample